Product Design with Multiple Quality-Type Attributes - Kim, Kilsun; Chhajed, Dilip (Management Science, 2002)
We consider a product line design problem with multiple attributes for a monopolist serving a market with two customer segments. Products are designed with quality type attributes for which more is always better than less. By considering multiple attributes, we derive a measure of multidimensional customer preference and offer insights into the optimal product design. When customers'preferences exhibit different orders in different attributes, our results show that products are differentiated horizontally where no one product is better than the other with respect to all attributes, and that there exists a region where the first-best solution for the monopolist is feasible despite the problem of cannibalization. Furthermore, single-product offering strategies are never optimal, so pooling of customer segments or reduction of the number of segments served will not occur.